The influence of three acid modifications on the physicochemical characteristics of tea-waste biochar pyrolyzed at different temperatures: a comparative study. Issue 31 (4th June 2019) - Peiris, Chathuri; Nayanathara, Oshani; Navarathna, Chanaka M.; Jayawardhana, Yohan; Nawalage, Samadhi; Burk, Griffin; Karunanayake, Akila G.; Madduri, Sunith B.; Vithanage, Meththika; Kaumal, M. N.; Mlsna, Todd E.; Hassan, El Barbary; et al.
Abstract : Tea-waste biochar produced under different pyrolysis temperatures were subjected to three acid modifications and a comparative evaluation of their key physicochemical characteristics made. Abstract : Tea-waste is an abundant feedstock for producing biochar (BC) which is considered to be a cost effective carbonaceous adsorbent useful for water remediation and soil amendment purposes. In the present study, tea-waste BC (TWBC) produced at three different temperatures were subjected to nitric, sulfuric and hydrochloric acid modifications (abbreviated as NM, SM and HM respectively). Characteristics of the raw and modified BC such as ultimate and proximate analyses, surface morphology, surface acidity and functionality, point of zero charge, cation exchange capacity (CEC) and thermal stability were compared to evaluate the influence of pyrolysis temperature and of modifications incorporated. The amount of carboxylic and phenolic surface functionalities on TWBC was seen to decrease by 93.44% and 81.06% respectively when the pyrolysis temperature was increased from 300 to 700 °C. Additionally, the yield of BC was seen to decrease by 46% upon the latter temperature increment. The elemental analysis results provided justification for high-temperature BC being more hydrophobic as was observed by the 61% increase in H/C ratio which is an indication of augmented aromatization. The CEC was the highest for the low-temperature BC and was seen to further increase by NM which is attributed to the 81.89% increase in carboxylic functionalities. The surface area was seen to significantly increase for BC700 upon NM (∼27 times). The SM led to pore wall destruction which was observed in scanning electron microscopy images. Findings would enable the rational use of these particular modifications in relevant remediation and soil amendment applications.